Predictive soil mechanics proceedings of the Wroth Memorial Symposium held at St Catherine's College, Oxford, 27-29 July 1992 - Houlsby, G. T.; Schofield, A. N. 1930-; Wroth, Peter (Thomas Telford, 1993)
This volume contains the 49 papers which form the proceedings of the Wroth Memorial Symposium. The themes of the symposium were soil properties and their measurement, especially means of in-situ tests, prediction and performance, and design methods.